Black people and secure psychiatric facilities. Patterns of processing and the role of stereotypes - Boast, Neil (The British journal of criminology, 1995)
Afro-Caribbeans and Africans form a greater proportion of patients in secure psychiatric hospitals, compared to their representation in the general population of England and Wales. Research evidence is marshalled from the fields of psychiatry and criminology to produce an explanatory model for this finding. A simple theory based solely on the assumption of racist practice is insufficient. Multiple factors and their interaction need to be considered. Crucial to an understanding are those which influence both the mode of presentation to psychiatric services and the use of compulsory detention under the 1983 Mental Health Act. They include rates of arrest and subsequent conviction, the provision and uptake of mental health services, diagnostic practices, and the role of stereotypes. Underlying socio-economic considerations are highlighted where relevant. At each stage of processing by the criminal justice and psychiatric systems, there is an apparent incremental increase in discrimination. It is argued, however, that background variables are more significant than ethnicity alone. They operate through the formation of stereotypes, which modify social judgments. The implication of this model is that over-representation cannot be addressed purely by a modification of admission practices of secure psychiatric facilities. More fundamental and wide-ranging solutions need to be sought